Knowledge and Behavior Aspect Related to Scabies Incidence in Syamtalira Bayu Health Center, Northern Aceh Regency - Noviana Zara (HM Publisher, 2022)
Scabies is a contagious skin infection caused by the parasite Sarcoptes scabiei and the most common cause of itchy skin. Factors that influence the high prevalence of scabies in developing countries are related to poverty which is associated with low levels of hygiene, difficult access to water, and residential density. This study aimed to determine the knowledge and behavior related to scabies incidence in Syamtalira Bayu Health Care Center, Northern Aceh. This research is an observational study with descriptive design. The study was carried out in October 2019 at the Syamtalira Bayu Community Health Center, Northern Aceh regency, Indonesia. A total of 100 respondents were participated in this study. The inclusion criteria were man and woman aged 16-45 years, lived in Syamtalira Bayu regency and agreed to participate in study. Fifty percent of respondents suffered from scabies. Most of them had behavior related scabies, such as alternating prayer tools (70%), alternating towels (53%), and sleeping together (64%). The knowledge level in people of Syamtalira Bayu Regency is good. However, they did not apply and practice the knowledge into their daily life, as seen on behavior related incidence scabies is still high.